2020
DOI: 10.18039/ajesi.682059
|View full text |Cite
|
Sign up to set email alerts
|

Matematik Dersi Öğretim Programı Üzerine Meslek Lisesi Matematik Öğretmenlerinin Görüşleri

Abstract: In this study, it was aimed to get opinions of Vocational and Technical Anatolian High Schools' mathematics teachers about mathematics curriculum. In this respect, it has been benefited from case study from qualitative research methods and maximum variation sampling. The study group consisted of 14 mathematics teachers working in the Eskisehir city center and a semistructured interview form was used as data collection tool. Teachers evaluated positively getting opinions of stakeholders for updating curriculum.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The points to be considered in evaluation are expressed differently by each curriculum and the commonly stated expression is 'evaluation which is a part of the learning process and should be done continuously'. It has been concluded that in line with previous researches, there is not sufficient information on the evaluation and assessment process in Turkish SMC (Biçer & Ada, 2020;Çiftçi et al, 2013). Adding methods related to evaluation and assessment to the curriculum will make mathematics education more efficient as it will guide teachers better.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…The points to be considered in evaluation are expressed differently by each curriculum and the commonly stated expression is 'evaluation which is a part of the learning process and should be done continuously'. It has been concluded that in line with previous researches, there is not sufficient information on the evaluation and assessment process in Turkish SMC (Biçer & Ada, 2020;Çiftçi et al, 2013). Adding methods related to evaluation and assessment to the curriculum will make mathematics education more efficient as it will guide teachers better.…”
Section: Discussionmentioning
confidence: 51%
“…Turkish SMC provides information related to the approaches, methods, and techniques used but does not mention where and how they can be used. In a sense, although it is thought that it gives the teacher flexibility in this subject, it has been stated in the studies that the teachers feel incomplete and want to receive in-service training on the learning-teaching process (Biçer & Ada, 2020). It has been understood that teachers could not benefit from this, especially regarding information and communication technologies (Çiftçi & Tatar, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kart ve Şimşek (2020) de matematik öğretim programlarını değerler bağlamında incelemiş ve kazanımlarda ve diğer kısımlarda değerlerin yeterince vurgulanmadığını belirtmiştir. Bu durum öğretmenlerin öğrenme yaşantılarında değerleri nasıl işe koşacaklarını anlamalarını güçleştirmektedir (Biçer & Ada, 2020). Ayrıca MDÖP'de etkinliklerin hem az oluşu hem de çeşitliliğinin olmaması dikkat çelici bir diğer bulgudur.…”
Section: Sonuç Tartışma Ve öNerilerunclassified
“…2000'li yıllardan itibaren eğitim öğretimi iyileştirme alanı olarak görülen matematik dersi öğretim programları 2005 yılında hem ilköğretimde hem de ortaöğretimde değişirken (Talim Terbiye Kurulu Başkanlığı [TTKB], 2005), bu programının revize edilmesiyle ilköğretim matematik programı 2009, ortaöğretim matematik programı 2011'de tekrar değiştirilmiştir (Baş, 2017;Şen, 2017;TTKB, 2009;TTKB, 2011;Yazıcılar & Bümen, 2017). 2012 yılında 4+4+4 sistemine geçilmesi ile 2013 yılında kademelere göre ayrı programlar hazırlanmış (ilkokul/ortaokul/lise), 2017 yılında temel eğitim (ilkokul/ortaokul) ve ortaöğretim programları tekrar değiştirilmiş ve 2018 yılında 2017 programı revize edilerek uygulanmaya başlanmıştır (Aydın ve diğerleri, 2018a;Bal ve diğerleri, 2021;Biçer & Ada, 2020;TTKB, 2013;TTKB, 2017a;TTKB, 2018) (Bu makalenin yazılması sırasında tüm sınıflardaki öğretim programlarının yenileceği açıklanmış olsa da, henüz kamuoyuyla paylaşılmamıştır). Son yapılan değişikliğin gerekçesi, bireyin ve toplumun değişen ihtiyaçlarının karşılanması için öğrenme / öğretme teori ve yaklaşımlarındaki yenilik ve gelişmeleri yansıtmaktır (TTKB, 2017b).…”
unclassified